Post-marketing surveillance for the safety of the 9-valent human papillomavirus vaccine: a retrospective real-world study in China - Ruogu Meng; Rui Ma; Jianmei Wang; Peipei Liu; Zuoxiang Liu; Bingjie He; Zhike Liu; Yu Yang; Siyan Zhan (Taylor & Francis Group, 2023)
Background The 9-valent human papillomavirus (9vHPV) vaccine was introduced in China in 2018. This study was conducted to monitor the occurrence of new-onset autoimmune diseases (AIs) in Chinese women vaccinated with the 9vHPV vaccine and adverse pregnancy outcomes in infants born to mothers with inadvertent pregnancy exposure. Research design and methods Women who received the first dose of the 9vHPV vaccine at age 16-26 years in Ningbo between January 2019 and March 2021 were monitored in the Ningbo Regional Health Information Platform. New-onset cases of seven pre-specified AIs diagnosed within six months after vaccination were collected. Cases of stillbirth and 23 major congenital anomalies diagnosed within three months of birth in target infants were collected. Results A total of 102,670 doses of the 9vHPV vaccine were administered to 41,609 women who had received no other HPV vaccine. New-onset AIs were diagnosed in 36 women, comprising 21 Hashimoto's, 11 Graves', and 4 uveitis disease cases. Among 50 women with maternal vaccination exposure, no stillbirths were observed. One case of microtia was observed. Conclusions In this first post-marketing surveillance of the 9vHPV vaccine in China, no safety signals were identified when putting the results in context to published data.